THE EFFECT OF THE SYLLABIC METHOD ON THE EARLY READING SKILLS OF EIGHTH-GRADE STUDENTS WITH INTELLECTUAL DISABILITIES AT A SPECIAL SCHOOL IN SURAKARTA - Arvia Roosiana; Munawir Yusuf; Dewi Sri Rejeki (Journal of Disability, 2025)
This research is motivated by the low initial reading ability of eighth grade students at Surakarta Special School, where all students still have difficulty in recognizing letters and often make mistakes in distinguishing letter shapes. Based on these problems, the researcher aims to determine the effect of implementing learning with the syllabic method to influence the improvement of initial reading ability in eighth grade mentally retarded children at SLB C SETYADARMA Surakarta. This research uses a quantitative approach with an experimental design in the form of a one-group pretest-posttest design. The validity test used in this study is content validity with the Aiken's V formula obtained an average value of 0.94. While the reliability test uses Cronbach Alpha which shows a significance value of 0.884. Data collection was carried out using an oral test instrument. The data analysis technique used to test the research hypothesis is the Wilcoxon Sign Rank Test. The results of the study showed an increase in initial reading ability after the syllabic method was applied. This finding indicates that the use of the syllabic method has a positive effect on improving the initial reading ability of mentally retarded children. The advantage of this method lies in its approach, which focuses directly on syllables rather than letter-by-letter spelling, thereby accelerating the reading learning process for children with special needs. Thus, the syllabic method can be used as an effective alternative reading learning method for students with intellectual disabilities.